درجة ممارسة الكفايات التكنولوجية لدى أساتذة المرحلة الابتدائية في ظل الإصلاحات - بوعزة, صالح (University of Eloued جامعة الوادي, 2023)
تهدف هذه الدراسة إلى التعرف على أهم الكفايات التكنولوجية اللازمة لأساتذة التعليم الابتدائي في ظل الإصلاحات التربوية الجديدة ،ولتحديد الكفايات التكنولوجية اللازمة تم استخدام استبانة تضمنت في صورتها النهائية 32 فقرة طبقت على عينة عشوائية تكونت من 87 أستاذ وأستاذة ببعض ابتدائيات مدينة باتنة ، وبعد التحليل الاحصائي للبيانات دلت النتائج أن مجالات أداء المهارات الحاسوبية ،و الوسائل التعليمية باستخدام الحاسب في العملية التعليمية تمثل كفايات بدرجة ممارسة عالية، أما وسائل الاتصال فهي بدرجة ممارسة متوسطة ، كما توصلت الدراسة إلى أن درجة ممارسة الكفايات التكنولوجية لدى أساتذة التعليم الابتدائي من وجهة نظرهم كانت عالية. This study aims to identify the most important technological competencies required for teachers of primary education in light of the new educational reforms, and to determine the necessary technological competencies, a questionnaire was used that included in its final form 32 paragraphs applied to a random sample consisting of 87 male and female teachers in some elementary schools in the city of Batna, and after statistical analysis of the data The results indicated that the areas of performance of computer skills and teaching aids using the computer in the educational process represent competencies with a high degree of practice, while the means of communication are with a medium degree of practice.
مقال